Trends in the incidence of acute watery diarrhoea in the Lao People's Democratic Republic, 2009–2013 - Houatthongkham, Souphatsone; Sithivong, Noikaseumsy; Jennings, Gregory; Phengxay, Manilay; Teepruksa, Phanthaneeya; Khamphaphongphane, Bouaphanh; Vongphrachanh, Phengta; Southalack, Kongmany; Luo, Dapeng; Chiu, Cindy H (Western Pacific Surveillance and Response, 2016)
Diarrhoeal disease is the second leading cause of death in children under age 5 worldwide, with rotavirus being the main etiology. In the Lao People's Democratic Republic, acute watery diarrhoea (AWD) was introduced as one of the national notifiable diseases in 2004. We retrospectively reviewed the aggregate (n = 117 277) and case-based (n = 67 755) AWD surveillance data from 2009 to 2013 reported weekly from 1115 health facilities nationwide. Rotavirus rapid test data from all eight sentinel sites in Vientiane Capital in 2013 were also collected for analysis. The incidence of AWD ranged between 215 and 476 cases per 100 000 population and increased from 2009 to 2012 when it levelled off. The most affected age group was children under 5 who were about seven to nine times more likely to have AWD than the rest of the population (P